Comparative study of intra-articular pressure dynamics in joints with acute traumatic and chronic inflammatory effusions: potential implications for hypoxic-reperfusion injury. Issue 12 (December 1991) - Merry, P; Williams, R; Cox, N; King, J B; Blake, D R
Abstract : It has been proposed that the process of hypoxic-reperfusion injury contributes to the persistence of synovitis in the inflamed human joint. The generation of pathological, exercise induced, intra-articular pressure leading to occlusion of the synovial microcirculation is central to this mechanism. However, acute traumatic inflammatory joint effusions rarely result in chronic synovitis, suggesting that either the basic hypothesis is incorrect, or that joints with acute traumatic effusions show different intra-articular pressure dynamics. In this study the intra-articular pressure was measured at rest and during isometric exercise in five patients with acute traumatic joint effusions and in nine patients with chronic inflammatory joint effusions. The generation of intra-articular pressure in the patients with acute traumatic effusions was significantly lower at rest (mean 2.0 v 19.6 mm Hg) and during exercise (mean 13.7 v 222.5 mm Hg) than in the patients with chronic effusions. This was due to reflex muscular inhibition around the joint, which inhibited the pathological generation of intra-articular pressure. This difference in the ability to generate intra-articular pressure might mitigate against hypoxic-reperfusion injury in joints with acute traumatic effusions, thereby explaining the paradoxical clinical observation that patients with acute traumatic inflammatory joint effusions rarely develop chronic synovitis.